Converging alternatives : the Bund and the Zionist Labor Movement, 1897-1985 - Gorni, Yosef (SUNY series in Israeli studies., 2006)
"Converging Alternatives provides the first comparative study of the national ideology of two rival Jewish socialist movements: the Bund party and the Zionist Labor movement in Eretz-Israel (Palestine). Yosef Gorny traces the concept of the Jewish nation from the foundation of the Bund and the first Zionist Congress in 1897 until the remains of the Bund decided to join the Jewish local and world institutions in 1985. The following events from those years are covered: the Soviet Revolution, the Balfour declaration, the founding of the Polish Republic, the British Mandate on Palestine, the rise of the Nazi party in Germany, the Jewish-Arab conflict, the Holocaust, and the gradual disappearance of the two movements from the historical stage. This approach to the Bund and Zionist movements helps explain the connection between nationalism and multiculturalism in the Jewish modern tradition."--BOOK JACKET.